Implementation of Cash Waqf in Improving Access and Quality of Al-Qur'an Education - Mursidi, Mursidi; Tanjung, Hendri; Supriyanto, Trisiladi (Fakultas Agama Islam, Universitas Ibn Khaldun Bogor, 2025)
Waqf in Islam is a Shari'a that is highly recommended and waqf is one of the financial instruments in the Islamic treasury apart from zakat, infaq and alms. Waqf and zakat also have different characters, but both are Islamic financial instruments. Zakat is consumptive in nature where it is distributed to consumption items so that its benefits are not sustainable, while waqf from the start is required to be productive and sustainable, that is, it survives if its assets and the results of its management are distributed in the form of assets and benefits so that the waqf can survive and continue to provide continuous benefits. This research aims to analyze the application of cash waqf in improving access and quality of Al-Qur'an education. This research was conducted at the Tahfidz Al-Qur'an Ibnu Jauzi Dramaga Islamic Boarding School in Bogor with 42 respondents. The research method used was a quantitative approach. Quantitative analysis is used with simple linear regression with data collection techniques through distributing questionnaires, observation and documentation. The results of the research show that the management of cash waqf in this Islamic boarding school has had a positive impact on increasing access and quality of Al- Qur'an education. The results of this research also show that cash waqf has a strong positive correlation or relationship with increasing access and quality of Al-Qur'an education.